Neonicotinoid pesticides in African agriculture: what do we know and what should be the focus for future research? - Orikpete, O.F.; Kikanme, K.N.; Falade, T.D.O.; Dennis, N.M.; Ewim, D.R.E.; Fadare, O.O. (Elsevier, 2025)
This review provides a comprehensive overview of the direct and indirect effects of neonicotinoid pesticides (NEO-P) within African agricultural ecosystems and identifies research gaps, particularly in the monitoring and regulation of pesticide use. We observed a decline in the numbers of NEO-P studies conducted in Africa since 2019 with 40.7% of the countries reporting at least one study to date. Imidacloprid (33.5%), acetamiprid (23.3%), and thiamethoxam (25.0%) are the most reported NEO-P across the continent with concentrations range from 9.0 × 10−5 to 7.2 × 107 mg kg−1, 1.7 × 10−5 to 2.1 × 103 mg kg−1, and 1.0 × 10−5 to 4.7 × 104 mg kg−1, respectively. NEO-P have been reported in honey, water, vegetables, fruits, and staple foods in most countries and in 92–100% of human urine samples collected in Ghana and Cameroon. This widespread presence indicates a potential food safety and public health concern, warranting further study. Studies on NEO-P interactions with bees have emanated mainly from North Africa (35.3% published studies) while Central/Middle, and Southern Africa accounted for 11.8% each of these studies, all of which were conducted in Cameroon and South Africa, respectively. It is important to have contextual evidence to understand neonicotinoids-pollinator interactions across specific African regions and countries; however, literature regarding the extent of NEO-P toxicities/effects on pollinators is required in 44 African countries. The environmental persistence of NEO-P and their broad-spectrum impact necessitate a re-evaluation of current regulatory practices and adoption of more sustainable pest management strategies across the continent. Furthermore, future studies should focus on investigating the long-term exposure to NEO-P, advanced computational methods in ecological risk assessments and eco-friendly alternatives to NEO-P.